Using of Cartoon Strip Media to improve in English Language Learning in Senior High Schools - Alias, Hamzah; Amiruddin; Satriani; Khair, Ummul; A, Marya (Education and Talent Development Center of Indonesia, 2022)
The preliminary and needs study found that partner schools required genuine media in the classroom with appealing colors. As a result, the goal of this service is to develop English vocabulary as well as the quality of cartoon strips as a learning tool. This community service project involves teaching children about Cartoon Strip Media in order to improve their English skills. Students from Madrasah Aliyah As'Adiyah Sengkang do this function. The findings suggest that cartoon strips as a form of English language learning medium are appropriate for MA students. It may be concluded that comic strips can be used as a medium in the classroom to improve vocabulary skills and student learning results, particularly in English language acquisition.